Impact of Capital Structure on Profitability: A Study on Listed Manufacturing Companies on Colombo Stock Exchange in Sri Lanka - Kengatharan, L. (Science for Sustainability University of West Hungary International Scientific Conference for PhD Students March 19-20, 2013 – Győr, 2013)
This paper empirically investigated the relationship between capital structure and the profitability of manufacturing companies in Sri Lanka, using panel data extracted from the financial statements of the companies listed on the Colombo Stock Exchange. Cross sectional design was adopted and the random sampling technique was used to collect data covering the five years period from 2006 to 2010. Firms’ profitability was measured by Return on Equity (ROE). These panel data were analyzed using Ordinary Least Squares (OLS) as a method of estimation. Results revealed that there was statistically significant negative relationship between long term debt and profitability. The relationship between total debt and the firm profitability were also found negatively related. Notwithstanding, results did not support any significant relationship between the short term debt and profitability. The effect of firm's age and size had considered as two control variables on the profitability scales. Firm size positively impacted on profitability and there was no clear evidence to impact the companies’ age on profitability. The outcomes of the study would guide entrepreneurs, loan- creditors and policy planners to formulate better policy decisions in respect of the mix of debt and equity capital and to exercise control over capital structure planning and thereby to control and reduce bankruptcy costs. The future research work based on this study is also suggested as identifying the optimum capital structure that leads to higher profitability in Sri Lanka.
Keywords: Short term debt; Long term debt; Total assets; Return on equity